A CROSS-SECTIONAL STUDY ON MENTAL HEALTH AND CARDIOVASCULAR REACTIVITY AMONG FRESH RESIDENT DOCTORS DURING COVID19 PANDEMIC IN INDIA - KUMAR, SUMIT; BANERJEE, ARIJITA; AHMAD, AQUIL (International Journal of Current Pharmaceutical Research, 2021)
Objective: The adverse psychological impact in doctors battling the Corona Virus Disease 2019 (COVID 19) epidemic arise from various social and administrative issues like excessive workload, inadequate interpersonal communications, biased work culture and lack of social support thus raising a warning of the mental health in doctors. The present study was done to assess the mental health and stress reactivity among the resident doctors who have been working for a prolonged duration during covid 19 pandemic in India. Methods: The subjects included 162 young resident doctors both males and females, of age group between 25-30 y, among which 92 were posted in covid wards on a rotation basis from 1st April 2020 to 31st December 2020 and 70 were doing duty in regular non-covid wards or not had done even a single duty in covid ward during the above period. All participants completed an online questionnaire that included the Beck Anxiety Inventory (BAI), the Beck Depression Inventory (BDI)–II, Connor-Davidson resilience scale (CDRISC) and Social Support Rating Scale (SSRS) followed by a cold pressor test to assess stress reactivity. Results: There were significant differences in the mental health and stress reactivity scores with lower resilience scores, lower social support rating scores, increased anxiety and depression in Covid ward doctors (p=0.001). Conclusion: The ﬁndings suggested high levels of training, resilience helpful social support and unbiased work culture were necessary to health care workers engaged in public health emergence.